2017
DOI: 10.1007/s11548-017-1540-6
|View full text |Cite
|
Sign up to set email alerts
|

Instrument-mounted displays for reducing cognitive load during surgical navigation

Abstract: Purpose Surgical navigation systems rely on a monitor placed in the operating room to relay information. Optimal monitor placement can be challenging in crowded rooms, and it is often not possible to place the monitor directly beside the situs. The operator must split attention between the navigation system and the situs. We present an approach for needle-based interventions to provide navigational feedback directly on the instrument and close to the situs by mounting a small display onto the needle. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…This setup creates a situation in which the surgeon is forced to focus both on the surgical field and the virtual planning simultaneously: the switching focus problem. 17,18 Another disadvantage is that the virtual planning presented on the 1 Radboud University Medical Center, Nijmegen, Netherlands 2 Academic Medical Center, Amsterdam, Netherlands monitors is often not aligned with the viewpoint of the surgeon. The surgeon must relate these positions mentally, which may hamper his or her intuitive interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…This setup creates a situation in which the surgeon is forced to focus both on the surgical field and the virtual planning simultaneously: the switching focus problem. 17,18 Another disadvantage is that the virtual planning presented on the 1 Radboud University Medical Center, Nijmegen, Netherlands 2 Academic Medical Center, Amsterdam, Netherlands monitors is often not aligned with the viewpoint of the surgeon. The surgeon must relate these positions mentally, which may hamper his or her intuitive interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Herrlich et al investigated different alternatives to the conventional monitor-based approach. One approach mounted a small display directly on the instrument and was used to display a similar navigation aid as implemented in this work [22]. Another work used a flexible thin display that could be attached to the patient's body [21].…”
Section: Discussionmentioning
confidence: 99%
“…For example, several empiric studies have shown that when instructional materials are presented in a “split-attention” format (e.g. medical diagrams with explanatory text outside of the figure instead of embedded within) then the high cognitive demand of integrating the multiple sources of information can impair learning [18, 25]. The split attention effect is just one of many “effects” described by CLT that address the way in which information is presented to learners.…”
Section: Cognitive Load Theorymentioning
confidence: 99%